The Surface Crack Concrete Sleeper Detection System Using Arduino - Kamarudzaman, Aiman Muhammad Aqil; Yahya, Musli Nizam; Sabtu, Norhidayah (Progress in Engineering Application and Technology, 2025)
The safety and efficiency of railway operations rely heavily on the condition of concrete sleepers, which provide structural stability by distributing loads and maintaining track alignment. This study proposes a Surface Crack Concrete Sleeper Detection System using Arduino to address challenges posed by traditional manual inspection methods. The system integrates a high-resolution camera for capturing detailed images and a rotary encoder for precise measurement of sleeper chainage, all controlled by an Arduino-based platform. The system was tested at the Labu-Tiroi Section and successfully demonstrated its ability to detect cracks autonomously. This innovative approach enhances the efficiency and accuracy of railway maintenance, reduces costs, and ensures safety.